13th IEEE Symposium on Design and Diagnostics of Electronic Circuits and Systems 2010
DOI: 10.1109/ddecs.2010.5491760
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based sensitivity and worst-case analyses of automotive electronics

Abstract: Abstract-Simulation-based verification of electronic control units must face demands related to more functionality and less time to verify it. To ensure a reliable system, one must determine how the omnipresent, internal and external variations affect the target response, and find safe bounds for it. The main challenge is to optimally characterize a high number of sources of variation, with a reduced number of simulation runs. The paper conducts more efficient sensitivity and worst-case studies by applying con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A systematic approach to efficiently find corner cases is the use of Design of Experiments (DoE), e.g. in [25]. In this approach, statistical methods are used to analyze the existing simulation runs, and to determine inputs that likely are candidates for worst case parameters.…”
Section: B Worst Case Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic approach to efficiently find corner cases is the use of Design of Experiments (DoE), e.g. in [25]. In this approach, statistical methods are used to analyze the existing simulation runs, and to determine inputs that likely are candidates for worst case parameters.…”
Section: B Worst Case Analysismentioning
confidence: 99%
“…However, this has two problems: First, for n uncertainties it requires Therefore, a number of approaches has been investigated to overcome these issues, e.g. [25]- [28]. A systematic approach to efficiently find corner cases is the use of Design of Experiments (DoE), e.g.…”
Section: B Worst Case Analysismentioning
confidence: 99%
“…Nassif [20] showed an approach towards WCA, which leads to more realistic estimates of the electronic device and circuit performance changes. Rafaila et al [21] discussed experiment design concepts, and screening tests aimed at reducing the verification space size, whereas Maly et al [22] and Nassif et al [23] suggested a methodology for modelling random process fluctuations, together with its advantages and applications.…”
Section: Introductionmentioning
confidence: 99%